A comparative study of blood pressure submission between mobilec app users and non-users in Romania: a pilot cohort study - Serbanoiu, Liviu Ionut; Busnatu, Stefan Sebastian; Lacraru, Andreea Elena; Pana, Maria Alexandra; Guberna, Suzana; Trache, Dragos; Elena, Plesu; Andrei, Catalina Liliana; Sinescu, Crina (Frontiers in Rehabilitation Sciences, 2025)
IntroductionCardiovascular diseases (CVD) represent a major public health concern in Romania. Despite the importance of home blood pressure (BP) monitoring, adherence to this practice remains limited. With the growing availability of eHealth solutions, this study aimed to evaluate the user experience and engagement of individuals with and without CVD in using telemonitoring technology.MethodsA prospective cohort study was conducted involving 24 participants who used a smartwatch application for telemonitoring. In addition, 176 participants who did not use the application were surveyed through an online questionnaire to serve as a comparison group. Participants were included regardless of CVD status. Data collected included blood pressure submission frequency, app usage metrics, and daily step counts. The cohort using the smartwatch app was observed over a 60-day period.ResultsAmong the participants, 58.3% were male and 41.7% were female, with a mean age of 50.57 years. The average number of active app usage days was 47.5 out of 60, and blood pressure was submitted on average 31.79 days. The average daily step count was 4,624 steps. In comparison, the reference group (non-app users) submitted BP data on average 7.41 days out of 60. A positive correlation was observed between active usage and BP submissions in the app group, indicating higher engagement with the telemonitoring intervention. Variability in user involvement was noted, with moderate but periodic participation.DiscussionThis pilot study suggests that Romanian patients are more likely to engage with mobile health technologies for hypertension management compared to traditional care approaches. The use of telemonitoring devices was associated with greater adherence to vital sign reporting. However, limitations such as small sample size, potential self-selection bias, and lack of randomization must be considered. Further research with larger, randomized control trials and extended follow-up is necessary to validate these findings. Empowering patients through eHealth solutions, alongside clinician support, may help mitigate the burden of cardiovascular diseases in Romania.